Standarisasi Ekstrak Sarang Semut untuk Pemenuhan Mutu Ekstrak Menuju Obat Herbal Terstandar Antikanker - Lindawati, Novena Yeti; Murtisiwi, Lusia (Jurnal Farmasi Indonesia, 2016)
Dry extract of sarang semut (Myrmecodia pendens Merr & Perry) water/n-butanol fraction is native plant from Papua is proven to be active against cancer cells. This research aims to improve the quality of extracts of sarang semut become the raw material that meets the standards of medicinal plant extracts in the fulfillment of the quality of the extracts into anticancer Standardized Herbal Medicine / Obat Herbal Terstandar (OHT). Extraction with ultrasonic methods (1:10 with methanol) and fractionation with water:butanol (1:1) as much as 1:20. Standardization and data analysis based on parameters of the Medicinal Plant Extracts (Kepmenkes RI No: 55/Menkes/SK/I/2000) and BPOM RI Regulation No. 12, Year 2014 about quality requirements of traditional medicine. Dry extract of sarang semut (water/n-butanol fraction) met the standards of raw material preparation for OHT with organoleptics shaped dried extracts, dark brown color, aromatic smell, and has a sour-bitter taste. Moisture content was 9,259 Â± 0.001 (â?¤ 10%). Total Plate Count was 5 x 103 colonies/g (< 104 colonies/g). Yeast and Mold Count was 0,5 x 101 colonies/g (< 103 colonies/g). Pathogenic bacteria test shows that MPN Coliform value was 0 colonies/g and negatively to the presence of Escherichia coli, Salmonella sp, Staphylococcus aureus, Pseudomonas aeruginosa, and Shiggella sp. The extract was not detected the presence of aflatoxin total (aflatoxin B1, B2, G1 and G2). The content of heavy metal Cd was 0,0052 Â± 0.0005 ppm (â?¤ 0.3 ppm) and heavy metals Pb was 0,9429 Â± 0,0087 ppm (â?¤ 10 ppm).